TEKNIK RITMIS DAN SPASIAL UNTUK MEMBANGUN EMOSI KARAKTER PEMERAN PADA FILM “GENISMARA” - I Putu Andika Arya Pratama; I Ketut Buda; I Nyoman Payuyasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The phenomenon of pregnancy out of wedlock spreads because the association among teenagers today can be said to be concerning because of the proliferation of promiscuity which has an impact on the behavior of free sex. This results in the emotions of the perpetrator or in this case the couple outside of marriage being unbalanced, due to their young age. This can be dangerous if emotions are able to express or display behavior in accordance with what feelings he is experiencing. The editing concept that will be applied is to build the emotions of the cast's characters by applying rhythmic and spatial aspects of editing techniques in the film entitled “Genismara”. The process of creating this film through various methods, the first is a data search method by observing film works with the application of rhythmic and spatial techniques, the second is documentation of books, journals, theses. This is done to find out the sound or understanding of rhythmic and spatial techniques, after which it is continued with the method of creation, namely pre-production, production and post-production. This method is carried out to apply or implement rhythmic and spatial techniques. The results of the application of rhythmic and spatial techniques are, the two techniques have different ways of applying, the rhythmic aspect is the aspect that is able to control the length of the duration of a shot in other words emphasizing a moment, while spatial is manipulating the dimensions of the shot, when the two techniques are combined and matched. the scene scene 5, scene 7 scene 8 scene 14, scene 15, scene 16, scene 17, scene 20, scene 21, scene 22, scene 23 will generate or embody an emotion that build emotional character actor like tranquility, doubts and Fright.